If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2(3j + -2) = 49(1 + j) Reorder the terms: 6 + 2(-2 + 3j) = 49(1 + j) 6 + (-2 * 2 + 3j * 2) = 49(1 + j) 6 + (-4 + 6j) = 49(1 + j) Combine like terms: 6 + -4 = 2 2 + 6j = 49(1 + j) 2 + 6j = (1 * 49 + j * 49) 2 + 6j = (49 + 49j) Solving 2 + 6j = 49 + 49j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-49j' to each side of the equation. 2 + 6j + -49j = 49 + 49j + -49j Combine like terms: 6j + -49j = -43j 2 + -43j = 49 + 49j + -49j Combine like terms: 49j + -49j = 0 2 + -43j = 49 + 0 2 + -43j = 49 Add '-2' to each side of the equation. 2 + -2 + -43j = 49 + -2 Combine like terms: 2 + -2 = 0 0 + -43j = 49 + -2 -43j = 49 + -2 Combine like terms: 49 + -2 = 47 -43j = 47 Divide each side by '-43'. j = -1.093023256 Simplifying j = -1.093023256
| 4a^2-10a=0 | | 69.1=2*3.14*r | | 7-3(a+4)= | | t^2-7=18 | | 6y^3-21y^2-4y+14=0 | | -9=-5(8-2k)+3(k-7) | | 5x-20=10x+15 | | -5(3a+6)=-105 | | 9y=7y+24 | | 5+4t=7(t) | | -16x^2+60x=56 | | 4a+3(a-2)=2(3a-2) | | 2(4x+3)+4=3x(2x+4) | | 3(x-2)=9(9x+2) | | (-8+5i)(-7+3i)= | | 15-3(2x-9)+x=115 | | -16x^2+6x=56 | | 69.1=3.14*r | | 0.06(y-9)+0.20y=0.16y-0.01(60) | | -6.1x+108.8= | | 6(5n+7)-4(4n+6)=-24 | | 5+4n=7+n | | 4y+2+y=180 | | 19x-9x=20 | | 9x+8=x+40 | | -7.5x+102.3= | | 5+4n=7n | | -6(b-7)-2(b+6)=30 | | 6w+2-3w=26 | | -(3x-5)+2x=7 | | -4f+1= | | 4y+60=9y |